1991
DOI: 10.1161/01.cir.84.2.697
|View full text |Cite
|
Sign up to set email alerts
|

Diminishment of respiratory sinus arrhythmia foreshadows doxorubicin-induced cardiomyopathy.

Abstract: Background. The development of a microcomputer-based device permits quick, simple, and noninvasive quantification of the respiratory sinus arrhythmia (RSA) during quiet breathing.Methods and Results. We prospectively and serially measured the radionuclide left ventricular ejection fraction and the RSA amplitude in 34 cancer patients receiving up to nine monthly bolus treatments with doxorubicin hydrochloride (60 mg/m2). Of the eight patients who ultimately developed symptomatic doxorubicin-induced congestive h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 19 publications
2
15
0
1
Order By: Relevance
“…Heart rate variability was significantly impaired in patients who received 2400 mg/m2 doxorubicin and was the only parameter showing a correlation with cumulative dose. Similar results were reported by Hrushesky et al [24], who found that diminished respiratory sinus arrhythmia predicted congestive heart failure during treatment with doxorubicin. This suggests that HRV could be a sensitive index for cardiotoxicity.…”
Section: -Hour Ambulatory Eccsupporting
confidence: 90%
“…Heart rate variability was significantly impaired in patients who received 2400 mg/m2 doxorubicin and was the only parameter showing a correlation with cumulative dose. Similar results were reported by Hrushesky et al [24], who found that diminished respiratory sinus arrhythmia predicted congestive heart failure during treatment with doxorubicin. This suggests that HRV could be a sensitive index for cardiotoxicity.…”
Section: -Hour Ambulatory Eccsupporting
confidence: 90%
“…Effects of anthracycline therapy on HRV in humans have been reported previously [29][30][31][32][33]. Three of these studies were retrospective [29,31,32], and one study evaluated cardiac parasympathetic control [30].…”
Section: Discussionmentioning
confidence: 97%
“…According to the study of Hrushesky et al [65], it is unlikely that alterations in HRV were provoked by DOX-induced autonomic neuropathy. They proposed that the direct effect of DOX on the heart muscle itself caused HRV changes [65].…”
Section: Discussionmentioning
confidence: 99%